Analysis Of Factors Affecting the Performance of Women Entrepreneurs Based on Food in Batu Aji District, Batam City - Hati, Shinta Wahyu; Yuniarti, Ela (MID Publisher International, 2023)
The purpose of the research are: (1) to know and analyze the internal factors influence the performance of women entrepreneur based on food in Batu Aji district; (2) to know and analyze the external factors influence the performance of women entrepreneur based on food in Batu Aji district; (3) to know and analyze the external factors influence internal factors of the performance of women entrepreneur based on food in Batu Aji district. Total respondents are 77 which divided from four location in Batu Aji district. The sample technique uses purposive sampling. The analysis technique used structural equation modelling. The result indicate that: (1) internal factors which consist of human resource, marketing, finance, and production and operation have possitive affect to the performance of women entrepreneur; (2) external factors which consist of social and culture, business competition, and related institute role have possitive effect to the performance of women enterpreneur; (3) external factors of performance have possitive affect to internal factors of performance.